Spatial Inequality in Development of Robertsganj Tahsil, Sonbhadra District, U.P. - Singh, S.B.; Chandramauli (National Geographical Journal of India, 2022)
Development is a value-positive concept as it is not only a change but a change for better. Development as such is neither class-neutral nor it is uniformly available across the regions. The development process usually benefits some classes of the society more than other classes. Also, it helps certain regions to attain higher levels of development than other regions, resulting to both social and regional disparities. Even planned development in our country does not reduce regional disparities rather kept on growing rapidly in absence of concerted efforts on the part of the government to achieve equality in development. The present paper explores spatial inquality in development of Robertsganj tahsil and evaluates centralized development mechanism.